Physical activity in the management of obesity in prader-willi syndrome - Łuniewski, Bartosz; Macko, Angelika; Łuniewska, Maria; Lauko, Kamil; Olszańska, Monika; Nowicka, Iga; Jurczuk, Aleksandra (Quality in Sport, 2025)
Introduction: Prader-Willi syndrome (PWS) is a rare genetic disorder whose most characteristic and dangerous symptom is massive obesity. It develops as a result of neurohormonal abnormalities, abnormal appetite regulation and reduced energy expenditure. Due to its multifactorial nature, the treatment of obesity in PWS presents particular clinical challenges. Materials and methods: A review of selected literature in the PubMed database was conducted, using the following keywords: “Prader Willie Syndrom”, “Phisical excercise”, “Obesity”,”Treatment” Summary: This paper discusses the main mechanisms leading to the development of obesity in PWS, such as hypothalamic dysfunction, endocrine disruption (ghrelin, leptin, GH) and changes in body composition. Current therapeutic strategies - nutritional therapy adapted to the developmental stage of the patient, growth hormone treatment and the potential use of anti-obesity drugs - were analysed. Special attention was given to the role of physical activity, which, despite its limited effect on body weight, significantly improves fitness, muscle strength, body composition and quality of life in patients. Conclusions: The management of obesity in PWS requires an individualised, multidirectional approach based on collaboration between the specialist team and the family. Given the limited efficacy of available therapies, further research is needed into new treatments - both pharmacological and non-pharmacological - that are better adapted to the metabolic and behavioural specificities of this patient group.